68Ga-radiolabeled fluorescent dye for potential non-invasive multimodal imaging of subarachnoid hemorrhage - Jona Wilhelm Gerhards; Laura Schäfer; Daniel Kang; Ute Lindauer; Susanne Lütje; Felix Manuel Mottaghy; Tobias Schmidt; Andreas Theodor Josef Vogg (EJNMMI Radiopharmacy and Chemistry)
Abstract Background Aneurysmal subarachnoid hemorrhage (aSAH) is a distinct type of stroke, primarily caused by the rupture of a brain aneurysm. The underlying mechanisms of aSAH remain incompletely understood, prompting ongoing research in this area. Recent investigations into the perivascular system revealed a distribution disturbance of the dye Alexa Fluor™ 594 during measurements. To further investigate this distribution anomaly, it is proposed to label the dye with a radionuclide for biokinetic tracking in rats by means of positron emission tomography for enhanced imaging and analysis. Results The fluorescent dye Alexa Fluor™ 594 after chelator conjugation was successfully labeled with the positron-emitting radionuclide 68Ga(III) in a no-carrier-added form. Initially, the NODA-GA-NHS ester was employed to react with the amino group of Alexa Fluor™ 594 1,5-diaminopentane, facilitating subsequent radiolabeling with 68Ga. The formation of the Alexa Fluor™ 594-chelator conjugate, as well as the radiolabeling, were investigated as a function of reaction time and temperature. For potential animal experiments, it was necessary to increase the reaction temperature from room temperature to 80 °C to optimize the reaction conditions, given the short half-life of 68Ga. Optimal labeling conditions were established, achieving a radiochemical yield of > 85%. Separation and purification of n.c.a. [68Ga]Ga-NODA-GA-Alexa Fluor™ 594 were conducted, with impurities remaining below 3%. Conclusions This experimental approach successfully yields the desired radiolabeled dye, which is now available for animal studies, potentially offering enhanced insight into the mechanisms of aSAH.